Photo-catalysis water splitting by platinum-loaded zeolite A. (18th May 2018) - Cheng, Jing; Gao, Changda; Jing, Ming; Lu, Jian; Lin, Hui; Han, Zhaoxia; Ni, Zhengji; Zhang, Dawei
Abstract: Under the λ≥420 nm visible light illumination, the Pt 4+ ions exchanged LTA zeolite powders without further heat-treatment presented H2 evolution at a rate of 5 μl/(15 mg·h) via photocatalysis water splitting. It was shown that the efficiency of H2 generation by the Pt 4+ exchanged LTA zeolite powders without further heat-treatment was higher than the counterpart of the samples with heat treatment. In addition, the samples with lower Pt loading concentration showed higher H2 evolution rate than those of higher Pt loading did. The higher H2 evolution efficiency can be attributed to the effective isolation of water molecules and Pt at the atomic or the few atom 'cluster' scale by LTA zeolite's periodical porous structure, which ensures a more efficient electron transfer efficiency for H2 evolution. However, after extra heat treatment, the Pt atoms reduced from Pt 4+ in LTA zeolite's cavities may tend to migrate to the surface and then form nano-particles, which led to the lower H2 evolution efficiency.